1967
DOI: 10.1172/jci105633
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effects of Insulin on Adipose Tissue Segments and Isolated Fat Cells of Rat and Man*

Abstract: Summary. In vitro metabolism of glucose-1-'4C by adipose tissue into 14CO2 and total 14C lipids in rat and man was compared employing both adipose tissue segments and isolated fat cells prepared from the same donor. In the rat, the basal glucose metabolism and response to insulin decreased with increasing body weight for both adipose tissue segments and isolated cells. Regardless of age, the isolated cells exhibited a persistently higher metabolic activity. Of the parameters selected, conversion to CO2 was mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0
1

Year Published

1969
1969
1979
1979

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(14 citation statements)
references
References 7 publications
2
11
0
1
Order By: Relevance
“…Although pieces of fat responded to insulin no effects of insulin could be detected with fat cells. In this respect our data are similar to the observation of Gries and Steinke (23), who demonstrated a greater response in pieces of fat than in fat cells. Together these observations support the concept that the trauma involved in preparing fat cells might impair their sensitivity to insulin.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Although pieces of fat responded to insulin no effects of insulin could be detected with fat cells. In this respect our data are similar to the observation of Gries and Steinke (23), who demonstrated a greater response in pieces of fat than in fat cells. Together these observations support the concept that the trauma involved in preparing fat cells might impair their sensitivity to insulin.…”
Section: Discussionsupporting
confidence: 92%
“…Increased activity of this pathway during high caloric intake would tend to decrease the caloric effi- (20,21) depends calories may occur in normal man and animals. With upon the preparation chosen for study (22)(23)(24), upon human subjects they showed that high caloric intake the previous caloric intake, as well as age (23) and the leads to enhanced thermogenesis (17,18). The present size of fat cells (25).…”
Section: Discussionmentioning
confidence: 99%
“…Accompanying the aging process in man, there is a decline in glucose disappearance rate after either oral or intravenous glucose that is not caused by differences in insulin or glucagon secretion (23) and a decline in lipid synthesis by adipose tissue in response to insulin (24). The age-related changes in plasma acetate turnover that we observed may well be related to alterations in both glucose and lipid metabolism that occur during the aging process, and suggest that appropriate age-matched controls be included in all studies of acetate metabolism in the human.…”
Section: Discussionmentioning
confidence: 99%
“…The nature of the insulin resistance in obesity is unknown. Several recent studies have focused attention on the role of the expanded adipose tissue in the insulin resistance of obese humans (5,8) and experimental animals (9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%